Learning Tajwid and Murottal Al-Qur'an Science for Children in Wirakanan Village, Wirakanan Village, Kandanghaur District - Ahmad Kurnia (Konsultan Jurnal Ilmiah Indonesia, 2025)
Developing village potential towards a progressive society is something that must be considered. Students are expected to be able to understand every problem that occurs in society and make the best decisions to solve these problems with creative ideas. One form of student contribution in improving the quality of society is by carrying out community service programs.